Nilai Pendidikan Islam dalam Hadits-Hadits Kebolehan Membawa Anak di Masjid - Dirman, Dirman; Tetambe, Ahmad Ghifari (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2023)
In the view of Islam, one of the obligations that must be fulfilled by every Muslim is prayer. In order to be able to do it continuously every day, it takes discipline and habit. This study aims to describe the values of Islamic education in the hadiths regarding the permissibility of bringing children to the mosque. This research is a qualitative research library research by collecting data from books, journals and writings that are considered relevant. The results of this study indicate that the hadiths about the permissibility of bringing children to the mosque are closely related to the values of Islamic education. The values of Islamic education in question are religious education, moral education and social education.